2017
DOI: 10.1177/0886260517705663
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Physical Child Abuse Among Parents and Professionals in a French Emergency Department

Abstract: France has not prohibited all forms of corporal punishment, and the point at which an act is regarded as physical abuse is not clearly determined. The aim of our study was to compare perception of a caregiver's violent behavior toward his child by professionals and parents in an emergency department and determine characteristics associated with that perception. A cross-sectional study was conducted from November 2013 to October 2014 in the emergency department of the pediatric university hospital in Bordeaux, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…It was reported that sexual abuse (whether mild or severe) was considered as being more traumatic and severe if the parent was the perpetrator, yet the identity of the perpetrator did not affect perceptions of physical abuse. Bailhache, Alioum, and Salmi (2017) found that healthcare professionals often misdiagnosed victims of physical abuse due to personal perceptions and the variety of definitions to abuse. These studies' results suggest that people have widely varying beliefs or attitudes about what constitutes child maltreatment and its later consequences.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that sexual abuse (whether mild or severe) was considered as being more traumatic and severe if the parent was the perpetrator, yet the identity of the perpetrator did not affect perceptions of physical abuse. Bailhache, Alioum, and Salmi (2017) found that healthcare professionals often misdiagnosed victims of physical abuse due to personal perceptions and the variety of definitions to abuse. These studies' results suggest that people have widely varying beliefs or attitudes about what constitutes child maltreatment and its later consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Professionals may view such behaviors as less serious due to their specialized knowledge of child maltreatment (Giovannoni & Becerra, 1979; Pierce & Bozalek, 2004). Alternatively, the perception of behaviors as less serious could also reflect professionals’ greater tolerance of potentially abusive behaviors than the public (Bailhache et al., 2017). As professionals cope with the frequent exposure to cases of child maltreatment, they might also be inevitably desensitized toward maltreatment behaviors and may consequently perceive them as being less serious (Wright et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Pioneered by Giovannoni and Becerra (1979), the second group of studies examines differences in maltreatment perceptions across professional and public groups. These studies compared maltreatment perceptions across various professional groups, or across professional and public groups (e.g., Bailhache et al., 2017; Segal & Iwai, 2004). Other groups have also been sampled, with one recent study surveying maltreatment perceptions among children (Lev-Wiesel et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure child welfare workers' inconsistent judgements or assessments of case information, this study employs the perception of child abuse. Perception of child abuse is viewed as the embodiment of the complex influence of social environment characteristics and social norms (Bailhache, Alioum & Salmi 2020). The concept has been widely used to depict mandatory reporters' general awareness of child abuse (Alzoubi et al, 2018) and to examine the differences across regions and cultures (Fakunmoju & Bammeke, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%